PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN KARTU KUARTET TERHADAP PENINGKATAN PEMAHAMAN KAUSALITAS KELAS XI SMA NEGERI 7 SEMARANG - Dina Nur Asifah; Hany Nurpratiwi (SECONDARY: Jurnal Inovasi Pendidikan Menengah, 2026)
In addition to understanding historical content, students are required to develop historical thinking skills, particularly causal understanding. Learning media are not always dependent on digital technology, as obstacles may arise during implementation; therefore, alternative instructional media are needed. The purpose of this study is to measure the extent of the influence of using quartet card learning media on improving the understanding of causality among eleventh-grade students at SMA Negeri 7 Semarang. The study employed a quantitative approach using a quasi-experimental method with a nonequivalent control group design. Two classes were selected as the samples of this study. Class XI-8 served as the experimental class, while Class XI-7 served as the control class, with each class consisting of 36 students. The research instrument was an essay test at the C4 cognitive level (analysis), which had been tested for validity, reliability (Cronbach’s Alpha = 0.896), discriminating power, and difficulty index. The pretest and posttest data were analyzed using normality and homogeneity tests, followed by hypothesis testing through an independent samples t-test and N-Gain analysis. The results revealed that the significance value (2-tailed) was < 0.001 < 0.05, indicating that H₀ was rejected and H₁ was accepted. Furthermore, the N-Gain score was classified in the moderate category. These findings indicate that the use of Quartet Card media in history learning was moderately effective in improving students’ causal understanding in Class XI-8. Therefore, Quartet Card media may serve as an effective alternative instructional medium in history education by enhancing students’ comprehension, fostering a more engaging classroom environment, and providing meaningful historical learning experiences. ABSTRAK Selain memahami materi Sejarah peserta didik juga perlu untuk memiliki skill berpikir sejarah atau historical thinking terutama pemahaman kausalitas. Media pembelajaran tidak selamanya menggunakan media digital, namun bisa saja terdapat kendala ketika diterapkannya sehingga memerlukan alternatif media lainnya. Mengukur seberapa besar pengaruh penggunaan media pembelajaran kartu kuartet dalam meningkatkan pemahaman kausalitas kelas XI SMA Negeri 7 Semarang merupakan tujuan penelitian ini. Pendekatan penelitian yang digunakan kuantitatif jenis Quasi-eksperimen tipe nonequivalent control group design. Terdapat dua kelas terpilih menjadi sampel penelitian ini, kelas XI-8 berperan sebagai kelas eksperimen dan kelas XI-7 berperan sebagai kelas kontrol dengan banyak peserta didik yang sama yaitu 36 orang. Instrumen penelitian berupa soal esai dengan tingkat kemampuan kognitif di level C4 (menganalisis) yang telah di uji validitas, reliabilitas (Cronbach’s Alpha = 0,896), daya beda soal, dan tingkat kesukaran. Dilanjutkan uji analisis data pretest dan posttest menggunakan uji normalitas, uji homogenitas, uji hipotesis jenis independent sample t-test dan diakhiri uji N-Gain. Hasil analisis data menunjukkan hasil Signifikansi 0,001 < 0,05, sehingga H₀ ditolak dan H1 diterima di tambah nilai N-Gain masuk kedalam klasifikasi sedang. Artinya, penggunaan media pembelajaran berupa kartu kuartet pada mata pelajaran sejarah cukup efektif meningkatkan pemahaman kausalitas peserta didik kelas XI-8. Dengan demikian, media kartu kuartet dapat menjadi alternatif media pembelajaran sejarah yang efektif, mengembangkan pemahaman belajar, menghidupkan suasana kelas dan peserta didik mendapatkan pengalaman belajar sejarah yang berbeda.